Profiles of Exclusion and Social Inclusion Policies in Spain: Dimensions of Change - Gomà, Ricard; Rosetti, Natalia (Revista del CLAD Reforma y Democracia, 2016)
This article outlines, firstly, the European context of social inclusion policies, by means of a double perspective: comparative (diversity of welfare regimes) and dynamic (diversity of restructuring paths). On that basis, our analysis comprises two parts. On the one hand, the empirical foundations are traced: both the institutional map of the social inclusion policies in Spain, and the main profiles of poverty, exclusion and social inequality in Spanish and EU comparative perspective. On the other hand, we consider the challenges and the policy proposals to meet them. A threefold approach is developed: the policy frame, where the inclusion/ exclusion cleavage and the concept of new poverty are reinforced; the policy contents, where the alternatives are drawn in terms of human rights and personal autonomy (the new social services paradigm); and the governance dimension, with the option for new localism and action networks to implement social inclusion policies. The document offers a new set of variables emerging from the most intense years of crisis (2007-2012) and austerity (2010-2015). The growing gap between the impacts of the crisis-austerity policy regime, and the relative weakness of the social inclusion strategies across the diverse welfare models, leads us to sustain the case for a stronger social inclusion dimension, to play a central role within the new welfare cycle which is emerging in Europe.
Keywords: Inclusion; Poverty; Social Policy; Spain